Analysis of Assessment Results of Physical Education Learning Quality Mapping in Nahdlatul Ulama Pakis Junior High School - Akhmad Muhson; Sudari; Hendi Imam Fadoli; Nunuk Tujung Sari (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2024)
Learning Quality Mapping Cognitive Assessment is a cognitive assessment intended for the Malang Regency Education Office in mapping the quality of learning at the Junior High School level throughout Malang Regency, both public and private schools. The purpose of this research is that both students, teachers, schools and education agencies can find out the average achievement of student competencies in each subject. This research is included in ex-post facto research, this research uses a quantitative approach in the form of numbers. Ex-post facto research is a method that is widely used and useful for researchers because it provides a lot of valuable information for decision making in the field of education. The population and sample in this study were grade 9 students of Nahdlatul Ulama Pakis Junior High School totaling 178 and representative sampling was proportional random sampling.  Data collection in this study used primary data obtained from students in the form of questionnaires and secondary data obtained from documentation of learning outcomes obtained from teachers and research documentation. The data analysis technique used by this researcher is descriptive quantitative using questionnaires and documentation. The research results in of each class are in class 9A getting results with good predicates, class 9B getting results with good predicates, class 9C getting results with good predicates, class 9D getting results with good predicates, class 9E getting results with good predicates and class 9F getting results with good predicates. Thus it can be concluded that the learning process and learning outcomes of physical education at Nahdlatul Ulama Pakis Junior High School are going well as evidenced by the results of the assessment carried out simultaneously in Malang Regency in 2024.